MODEL PEMBELAJARAN GURU YANG KURANG VARIATIF DAN DAMPAKNYA TERHADAP PEMBELAJARAN MATEMATIKA - Badran, Rezki Farraj; Aisyah, Aisyah (PHI: Jurnal Pendidikan Matematika, 2026)
The learning models used by teachers play an important role in building students’ concentration, motivation, and learning engagement. However, various studies over the past ten years indicate that teachers still tend to use monotonous teaching models such as lectures, repetitive exercises, and assignment-based learning without variation. This condition has an impact on the decline of students’ learning concentration, especially in mathematics, which requires strong analytical skills and high levels of focus. This Systematic Literature Review (SLR) aims to map the development of research regarding the relationship between the lack of variation in teachers’ teaching models and students’ learning concentration at the elementary, junior high, and senior high school levels. Using sources from Google Scholar and SINTA (2015–2025), this SLR finds that less varied teaching models contribute to low learning focus, increased boredom, reduced attention to teacher explanations, and weakened understanding of mathematical concepts. On the other hand, the application of cooperative learning models, problem-based learning, technology-based learning models, and interactive learning models has been proven to improve students’ concentration and participation. The results of this study emphasize the importance for teachers to choose learning models that are relevant, adaptive, and varied in order to enhance students’ learning concentration.